Strategi Komunikasi Dakwah Televisi Komunitas An-Nur Masjid Agung Palembang - Syahir Badrudin; Riza Pahlevi; Sarminawati Sarminawati (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2017)
The researcher would like to know, first, how do the preach communication strategy applied in TV community Agung An-Nur Mosque in Palembang? Second, what are the preach programs in that TV? There some advantages from this research, first, theoretically, the result will add some more knowledge in preach and communication field. Second, practically, the result contributes positively for people in the field, personally or in group. The strategies are, conducting the strategies of An-Nur TV Palembang to have annually meeting discussing about funding, marketing target, and to do list. Another strategy is preparing some programs on air or off air. Additionally, some preach programs are Dakwah Akhbar, Uswatun Hasanah, Kekeran Ustadz, Keliling Masjid, Film Kartun Islami, Cawisan, Murotal al-Qur’an, Senandung Musik Islami.